Stopped-flow injection simultaneous determination of phosphate and silicate using molybdenum blue - Grudpan K. (2014)
Kinetic information for the phosphate - molybdate - ascorbic acid reaction can be obtained by making use of a very simple manually operated stopped-flow injection (FI) system. Various parameters (concentrations of reagents, flow rate, mixing coils, and volume of flow cell) were investigated for determination of phosphate. A stopped-FI system should be arranged for low degree of mixing (of reactants) and low dispersion so that good signals of rate changes will be observed. Simultaneous determination of phosphate and silicate by the stopped-FI technique is proposed, using a laboratory-made semi-automatic stopped-FI Analyzer with LED-based photometer. It is based on kinetic separation of phosphate and silicate using molybdenum blue. The proposed procedure has been demonstrated for the application to water samples. The results obtained agree with that of a standard method. © 2002 Elsevier Science B.V. All rights reserved.